The Effect of Kokami Learning Media (Mysterious Card Boxes) on the Learning Motivation of Junior High School Students - Meiliza Amelia Andariska; Ermis Suryana; Emilia Fitri (Global Journal of Islamic Education, 2026)
The background of this study is the low level of students’ learning motivation, which is indicated by students’ limited willingness to participate in learning activities, low motivation to achieve good academic results, lack of seriousness in completing assignments on time, as well as low enthusiasm and focus during the learning process. To address this problem, the Kokami (Mystery Card Box) learning media was implemented. This study aims to examine the effect of the Kokami (Mystery Card Box) learning media on students’ learning motivation.This study employed a quantitative research method with an experimental method using a Pre-Experimental Design, specifically the One Group Pretest–Posttest design. The sample consisted of 33 students. Data were obtained through observation guidelines, questionnaires, and documentation, and then analyzed using validity, reliability, and normality tests, along with hypothesis testing using the Paired Sample t-test.The research findings indicate that the average student learning motivation before the application of the Kokami (Mystery Card Box) learning media was 58.24, which was categorized as moderateand after the media was implemented, the average learning motivation increased to 63.85. The hypothesis testing the results indicated that the Sig. (2-tailed) value was < 0.001 < 0.05, and the comparison results indicated that t-count = 3.638 > t-table = 2.04; therefore, H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the use of the Kokami (Mystery Card Box) learning media on students’ motivation to learn. This study contributes by offering an alternative learning media that is effective in increasing students’ learning motivation and can be used as a reference for teachers in developing innovative instructional practices.